System społecznej odpowiedzialności według międzynarodowego standardu Social Accountability 8000 w Elektrowni Opole - Jastrzębska, Ewa Magdalena (Corporate Social Responsibility management system according to the international standard Social Accountability 8000 in Power plant Opole, 2007)
Unfavourable phenomena created by developing globalization, growing importance of multinational companies, caused the societies to inerease their expectations towards the enterprises. Companies willing to find themselves in the new reality should follow the idea of sustainable deveIopment what in the management system means Corporate Social Responsibility. The implementation of formalized management system conformable to the intemational standard SA8000 can be used as a confirmation on Corporate Social Responsibility. SA8000 is a standard for companies seeking to make the workplace morę humane as its mission is to improve working conditions and workers’ rights around the world. Among 7 enterprises in Poland having adopted SA8000 standard the special attention should be given to Power plant Opole, the first company in Poland which decided to implement this standard.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 507-515